2008
DOI: 10.1007/s00270-008-9462-x
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency Ablation Assisted by Real-Time Virtual Sonography and CT for Hepatocellular Carcinoma Undetectable by Conventional Sonography

Abstract: Real-time virtual sonography (RVS) is a diagnostic imaging support system, which provides the same cross-sectional multiplanar reconstruction images as ultrasound images on the same monitor screen in real time. The purpose of this study was to evaluate radiofrequency ablation (RFA) assisted by RVS and CT for hepatocellular carcinoma (HCC) undetectable with conventional sonography. Subjects were 20 patients with 20 HCC nodules not detected by conventional sonography but detectable by CT or MRI. All patients had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 20 publications
3
63
0
Order By: Relevance
“…However, RFA monotherapy may increase the risk of relapse in cases where the HCC is comparatively large, when it exists near the surface of the liver or near vessels that are hard to treat due to the risk of coagulation necrosis (8). A variety of methods, including imaging support such as Real-Time Virtual Sonography (9), have been devised in the past to counteract these difficulties.…”
Section: Introductionmentioning
confidence: 99%
“…However, RFA monotherapy may increase the risk of relapse in cases where the HCC is comparatively large, when it exists near the surface of the liver or near vessels that are hard to treat due to the risk of coagulation necrosis (8). A variety of methods, including imaging support such as Real-Time Virtual Sonography (9), have been devised in the past to counteract these difficulties.…”
Section: Introductionmentioning
confidence: 99%
“…Fusion imaging was first introduced by radiologists for the treatment of hepatic neoplasms or lesions [13][14][15][16][17]. To target hepatic lesions, especially when characterized by poor sonographic signal [18], they perform an US-guided, minimal invasive (e.g., RF ablation) procedure merging the iUS imaging with CT or other modalities.…”
Section: Discussionmentioning
confidence: 99%
“…However, the short durations of the different vascular phases, absence of real-time imaging guidance and increased radiation exposure are the disadvantages of using these imaging techniques. 78,79 To overcome these problems a method called "fusion imaging' or "real time virtual sonography", that synchronizes real-time US and CT or MRI, is introduced. 80 Two cohort studies showed an excellent technical success rate, safety and effectiveness for RFA using fusion imaging.…”
Section: Rfamentioning
confidence: 99%